Signaling pathways and advances in targeted therapy for adenomyosis - Li, Yue; Zhang, Hongyu; Ding, Yaoyao; Zhao, Yiling; Li, Yufeng; Qin, Tiansheng (Frontiers in Cell and Developmental Biology, 2025)
Adenomyosis is a common estrogen-dependent disease, characterized by the invasion of endometrial glands and stroma into the myometrium. It often results in dysmenorrhea, menorrhagia, and infertility, significantly impacting patients’ quality of life. Currently, the etiology and pathogenesis of adenomyosis remain unclear, and existing treatments have limitations. Therefore, further research on the mechanism and treatment of adenomyosis is urgently needed. Studies indicate that adenomyosis involves dysregulation of multiple signaling pathways, including VEGF, Wnt, PI3K, MAPK, NF-κB, cGAS-STING, TGF-β, Hedgehog, and Hippo pathways, which regulate processes such as estrogen and progesterone imbalance, angiogenesis, proliferation and invasion, and the processes of inflammation and fibrosis. This review summarizes the relevant signaling pathways involved in adenomyosis and discusses recent progress in targeted pathway therapies. Additionally, emerging therapeutic strategies such as multi-target combination therapy, epigenetic regulation, and natural products are emphasized as viable avenues for adenomyosis treatment in the future.